Dental student debt in the U.S.: A mountain to be scaled - David G Dunning (Wolters Kluwer Medknow Publications, 2013)
Dental student educational debt in the United States continues to grow as a concern for both dental educators and dental students. While certainly warranted, this concern needs to be understood from the perspective of return on investment. The student debt issue remains a critical one. However, this debt is essentially "good" debt when viewed as an investment made by associates/employees of general dental practices and general dental practice owners.